Theoretical analysis of correlations between two quantum fields exciting a three-level system using the cluster-expansion approach - Rose, Hendrik; Tikhonova, Olga V.; Meier, Torsten; Sharapova, Polina (Ultrafast Phenomena and Nanophotonics XXVI)

Coherent contributions to population dynamics in a semiconductor microcavity - Paul, J.; Rose, Hendrik; Swagel, E.; Meier, Torsten; Wahlstrand, J. K.; Bristow, A. D. (Physical Review B)

Super-Bloch oscillations with parametric modulation of a parabolic trap - Meier, Torsten; Ali, Usman (Condensed Matter)

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, Dirk Florian; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, Klaus; Reuter, Dirk; Schumacher, Stefan; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Helical Polariton Lasing from Topological Valleys in an Organic Crystalline Microcavity - Long, Teng; Ma, Xuekai; Ren, Jiahuan; Li, Feng; Liao, Qing; Schumacher, Stefan; Malpuech, Guillaume; Solnyshkov, Dmitry; Fu, Hongbing (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Manipulating polariton condensates by Rashba-Dresselhaus coupling at room temperature - Li, Yao; Ma, Xuekai; Zhai, Xiaokun; Gao, Meini; Dai, Haitao; Schumacher, Stefan; Gao, Tingge (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Pulse shaping for on-demand emission of single Raman photons from a quantum-dot biexciton - Praschan, Tom; Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Walther, Andrea; Schumacher, Stefan (Physical Review B)

Unidirectional vortex waveguides and multistable vortex pairs in polariton condensates - Gao, Xinghui; Hu, Wei; Schumacher, Stefan; Ma, Xuekai (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Switching Off a Microcavity Polariton Condensate near the Exceptional Point - Li, Yao; Ma, Xuekai; Hatzopoulos, Zaharias; Savvidis, Pavlos G.; Schumacher, Stefan; Gao, Tingge (ACS Photonics)

Nonlinear down-conversion in a single quantum dot - Jonas, Björn; Heinze, Dirk Florian; Schöll, Eva; Kallert, Patricia; Langer, Timo; Krehs, Sebastian; Widhalm, Alex; Jöns, Klaus; Reuter, Dirk; Zrenner, Artur

Electron polarons in lithium niobate: Charge localization, lattice deformation, and optical response - Schmidt, Falko; Kozub, Agnieszka L.; Gerstmann, Uwe; Schmidt, Wolf Gero; Schindlmayr, Arno (New Trends in Lithium Niobate: From Bulk to Nanocrystals)
Lithium niobate (LiNbO3), a material frequently used in optical applications, hosts different kinds of polarons that significantly affect many of its physical properties. In this study, a variety of electron polarons, namely free, bound, and bipolarons, are analyzed using first-principles calculations. We perform a full structural optimization based on density-functional theory for selected intrinsic defects with special attention to the role of symmetry-breaking distortions that lower the total energy. The cations hosting the various polarons relax to a different degree, with a larger relaxation corresponding to a larger gap between the defect level and the conduction-band edge. The projected density of states reveals that the polaron states are formerly empty Nb 4d states lowered into the band gap. Optical absorption spectra are derived within the independent-particle approximation, corrected by the GW approximation that yields a wider band gap and by including excitonic effects within the Bethe-Salpeter equation. Comparing the calculated spectra with the density of states, we find that the defect peak observed in the optical absorption stems from transitions between the defect level and a continuum of empty Nb 4d states. Signatures of polarons are further analyzed in the reflectivity and other experimentally measurable optical coefficients.

Bound polaron formation in lithium niobate from ab initio molecular dynamics - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (Applied Physics A)
Abstract Polarons influence decisively the performance of lithium niobate for optical applications. In this work, the formation of (defect) bound polarons in lithium niobate is studied by ab initio molecular dynamics. The calculations show a broad scatter of polaron formation times. Rising temperature increases the share of trajectories with long formation times, which leads to an overall increase of the average formation time with temperature. However, even at elevated temperatures, the average formation time does not exceed the value of 100 femtoseconds, i.e., a value close to the time measured for free, i.e., self-trapped polarons. Analyzing individual trajectories, it is found that the time required for the structural relaxation of the polarons depends sensitively on the excitation of the lithium niobate high-frequency phonon modes and their phase relation.
Keywords: General Materials Science; General Chemistry

Two-Mode Photon-Number Correlations Created by Measurement-Induced Nonlinearity - Meier, Torsten; Hoepker, Jan Philipp; Protte, Maximilian; Eigner, Christof; Silberhorn, Christine; Sharapova, Polina R.; Sperling, Jan; Bartley, Tim (Conference on Lasers and Electro-Optics: Applications and Technology)
We demonstrate theoretically and experimentally complex correlations in the photon numbers of two-mode quantum states using measurement-induced nonlinearity. For this, we combine the interference of coherent states and single photons with photon sub-traction.

DC Ionic Conductivity in KTP and Its Isomorphs: Properties, Methods for Suppression, and Its Connection to Gray Tracking - Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine; Eigner, Christof (Crystals)
We study the DC conductivity in potassium titanyl phosphate (KTiOPO4, KTP) and its isomorphs KTiOAsO4 (KTA) and Rb1%K99%TiOPO4 (RKTP) and introduce a method by which to reduce the overall ionic conductivity in KTP by a potassium nitrate treatment. Furthermore, we create so-called gray tracking in KTP and investigate the ionic conductivity in theses areas. A local unintended reduction of the ionic conductivity is observed in the gray-tracked regions, which also induce additional optical absorption in the material. We show that a thermal treatment in an oxygen-rich atmosphere removes the gray tracking and brings the ionic conductivity as well as the optical transmission back to the original level. These studies can help to choose the best material and treatment for specific applications.

LLC Resonant Converter Modulations for Reduced Junction Temperatures in Half-Bridge Mode and Transformer Flux in the On-the-Fly Morphing Thereto - Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Assessment of mechanical and optical properties of Al 6060 alloy particles by removal of contaminants - Vieth, Pascal; Borgert, Thomas; Homberg, Werner; Grundmeier, Guido (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Analyse des Versagensverhaltens geklebter Stahl- Verbindungen beim werkstoffschonenden Entfügen in der Karosserieinstandsetzung - Chudalla, Nick; Meschut, Gerson; Teutenberg, Dominik; Wibbeke, Michael; Bartley, Aurélie

Information Model for Hybrid Prototyping in Design Reviews of Assembly Stations - Gräßler, Iris; Roesmann, Daniel; Hillebrand, Stefan; Pottebaum, Jens (Procedia CIRP ICME)
Keywords: General Medicine

Entwicklung einer Methode zur Bewertung einer stahlintensiven Mischbau-Klebverbindung eines Batteriegehäuses gegenüber mechanischer und medialer Belastung unter Berücksichtigung der Interphasenstruktur - Schmolke, Tobias; Meschut, Gerson; Vieth, Pascal; Meinderink, Dennis; Grundmeier, Guido

Experimentelle und numerische Untersuchung der Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson; Kötz, Fabian; Matzenmiller, Anton; Damm, Jannis; Albiez, Matthias; Ummenhofer, Thomas

A Thermal Model for Recuperative Heat Engines Operating with Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Inguva, Venkatesh; Kenig, Eugeny Y. (Chemical Engineering Transactions)

CFD-Based Investigation of the Packing Microstructure Influence on Droplet Behavior and Film Flow - Dechert, Christopher; Kenig, Eugeny (Proceedings of the 12th international conference Distillation & Absorption 2022)

On Heat Regeneration Limitations in Heat Engines With Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Heat Powered Cycles Conference 2022)

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, Werner; Martins, P.A.F.; Bobbert, Mathias; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fiber reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processes.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Evaluation eines digitalen Fachspezifischen Chinesischsprachkurses für Studierende des Ingenieurwesens - Hambach, Dennis (die hochschullehre. Interdisziplinäre Zeitschrift für Hochschule und Lehre)
Ziel dieser Studie ist es den digitalen moodlegestützten asynchronen Sprachkurs Fachspezifisches Chinesisch für das „Maschinenbau in China Programm“ (mb-cn) der Fakultät für Maschinenbau der Universität Paderborn zu evaluieren, um Handlungsempfehlungen für zukünftig ähnlich aufgebaute Projekte zu entwickeln. Dazu wurden im Sommersemester 2021 sechs leitfadengestützte Interviews geführt. Die Interviews wurden anschließend mithilfe von deduktiv ermittelten Kategorien, die sich aus dem Technology Acceptance Model 2 (TAM2) nach Venkatesh und Davis (2000) ergaben, nach Mayring (2015) analysiert, um abschließend die Forschungsfrage zu beantworten: „Wie bewerten mb-cn Ingenieurstudierende die wahrgenommene Nützlichkeit der digitalen Sprachlernangebote des Kurses Fachspezifisches Chinesisch?“.
Keywords: Technology Acceptance Model; Fachspezifische Chinesischsprachkurse; digitale Lehre; Moodle; Evaluation

Geometric and mechanical joint characterization of conventionally and tumbled self-piercing riveting joints - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In view of economic and ecological trends, the concepts for lightweight construction in transport systems are becoming increasingly important. These are frequently applied in the form of multi-material systems, which are characterized by the selective use of materials and geometries. One major challenge in the manufacturing of multi-material systems is the joining of the individual components to form a complete system. Mechanical joining processes such as semi-tubular self-piercing riveting are frequently used for this application but reach their limits concerning the number of combinations of geometry and material. In order to react to the requirements and to increase the versatility of semi-tubular self-pierce riveting, a process combination consisting of a tumbling process and a self-pierce riveting process has been presented previously. This process combination is used in this work to investigate the versatility and to identify the influencing parameters on it. For this purpose, experiments are conducted to identify process-side influence possibilities. The tests are performed with a dual-phase steel aluminum alloy to represent the varying mechanical characteristics of multi-material systems. Furthermore, the initial sheet thicknesses of the joining partners are varied in several steps. In addition to the geometric joint formation used to describe the undercut, the rivet head end position and the residual sheet thickness, the joining process, is also analyzed during the investigations. Further, the innovative joining process is evaluated by comparing it with a conventional self-piercing riveting process. The knowledge obtained represents a basis for the identification and evaluation of the versatility of the process combination.
Keywords: Mechanical Engineering; General Materials Science

Extrahierung von Anforderungen aus natürlich-sprachlichen Lastenheften: Was erschwert eine KI-basierte Extrahierung? - Gräßler, Iris; Preuß, Daniel; Pottebaum, Jens (Softwaretechnik-Trends)

Energy saving potentials of an efficient recycling process of different aluminum rejects - Borgert, Thomas; Homberg, Werner (Energy Reports)
Keywords: General Energy

Review on mechanical joining by plastic deformation - Meschut, G.; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, W.; Martins, P.A.F.; Bobbert, M.; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Hot Spinning of Cutting Blades for Food Industry - Engemann, David; Homberg, Werner
The spinning process is a flexible incremental forming process for the manufacturing of axially-symmetric sheet metal or tubular components with functionally graded properties. It is characterized by the utilization of universal tooling geometries and quite low forming forces. The process has a high potential to reduce material waste, to extend the forming limits and to achieve more complex geometries as well as favorable part properties [1]. Current research work at the Chair of Forming Technology (LUF) is focused on innovative flow-turning processes that have a high potential for producing flat components with excellent geometrical and mechanical properties while keeping process times short [2]. In combination with process-integrated local heat treatment, the new spinning process is predestined for the efficient forming of ultra-high-strength steel or tailored materials. Due to the desired field of food industry only food-safe materials such as special stainless steels are being investigated. This paper presents an innovative machine layout as well as an adequate process design for the production of high-performance circular knives with optimized mechanical hardness. In this context, particular attention is paid to various areas of temperature control as well as process-related challenges during the process.
Keywords: Cutting blades; Flow-forming; Incremental forming; Hot Forming; High strength steels

Identification of Requirements for FE Modeling of an Adaptive Joining Technology Employing Friction-Spun Joint Connectors (FSJC) - Oesterwinter, Annika; Wischer, Christian; Homberg, Werner (Metals)
The adaptive joining process employing friction-spun joint connectors (FSJC) is a promising method for the realization of adaptable joints and thus for lightweight construction. In addition to experimental investigations, numerical studies are indispensable tools for its development. Therefore, this paper includes an analysis of boundary conditions for the spatial discretization and mesh modeling techniques, the material modeling, the contact and friction modeling, and the thermal boundary conditions for the finite element (FE) modeling of this joining process. For these investigations, two FE models corresponding to the two process steps were set up and compared with the two related processes of friction stir welding and friction drilling. Regarding the spatial discretization, the Lagrangian approach is not sufficient to represent the deformation that occurs. The Johnson-Cook model is well suited as a material model. The modeling of the contact detection and friction are important research subjects. Coulomb’s law of friction is not adequate to account for the complex friction phenomena of the adaptive joining process. The thermal boundary conditions play a decisive role in heat generation and thus in the material flow of the process. It is advisable to use temperature-dependent parameters and to investigate in detail the influence of radiation in the entire process.
Keywords: General Materials Science; Metals and Alloys

Further Development of an Adaptive Joining Technique Based on Friction Spinning to Produce Pre-Hole-Free Joints - Wischer, Christian; Homberg, Werner (Key Engineering Materials)
Mechanical joining processes are an essential part of modern lightweight construction. They permit materials of different types to be joined in a way that is suitable for the loads involved. These processes reach their limits, however, as soon as the boundary conditions change. In most cases, these elements are specially adapted to the joining point and cannot be used universally. Changes require cost-intensive adaptation of both the element and the process control, thus making production more complex. This results in high costs due to the increased number of auxiliary joining element variants required and reduces the economic efficiency of mechanical joining. One approach to overcoming this issue is the use of adaptive auxiliary joining elements formed by friction spinning. This article presents the current state of research on pre-hole-free joining with adaptive joining elements. The overall process chain is illustrated, explained and analyzed. Special attention is paid to demonstrating the feasibility of pre-hole-free joining with adaptive joining elements. The chosen mechanical parameters are subsequently listed. Finally, a comprehensive outlook of the future development potential is derived.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Comparative Analysis of Electrohydraulic and Electromagnetic Sheet Metal Forming against the Background of the Application as an Incremental Processing Technology - Heggemann, Thomas; Psyk, Verena; Oesterwinter, Annika; Linnemann, Maik; Kräusel, Verena; Homberg, Werner (Metals)
High-speed forming processes such as electromagnetic forming (EMF) and electrohydraulic forming (EHF) have a high potential for producing lightweight components with complex geometries, but the forming zone is usually limited to a small size for equipment-related reasons. Incremental strategies overcome this limit by using a sequence of local deformations to form larger component areas gradually. Hence, the technological potential of high-speed forming can be exploited for large-area components too. The target-oriented process design of such incremental forming operations requires a deep understanding of the underlying electromagnetic and electrohydraulic forming processes. This article therefore analyzes and compares the influence of fundamental process parameters on the acting loads, the resulting course of deformation, and the forming result for both technologies via experimental and numerical investigations. Specifically, it is shown that for the EHF process considered, the electrode distance and the discharge energy have a significant influence on the resulting forming depth. In the EHF process, the largest forming depth is achieved directly below the electrodes, while the pressure distribution in the EMF depends on the fieldshaper used. The energy requirement for the EHF process is comparatively low, while significantly higher forming speeds are achieved with the EMF process.

Automated Requirement Dependency Analysis for Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Hieb, Michael; Preuß, Daniel (Proceedings of the Design Society)
Abstract Requirements changes are a leading cause for project failures. Due to propagation effects, change management requires dependency analysis. Existing approaches have shortcomings regarding ability to process large requirement sets, availability of required data, differentiation of propagation behavior and consideration of higher order dependencies. This paper introduces a new method for advanced requirement dependency analysis based on machine learning. Evaluation proves applicability and high performance by means of a case example, 4 development projects and 3 workshops with industry experts.

Mensch-Tracking zur Identifizierung des Voranschreitens von Roboterunterstützten Rettungseinsätzen der Feuerwehr - Gräßler, I.; Roesmann, Daniel; Pottebaum, Jens; Corves, Burkhard; Mandischer, Nils; Gürtler, Marius (Tagungsband der VDI Mechatronik 2022)

Extended RFLP for complex technical systems - Gräßler, Iris; Wiechel, Dominik; Oleff, Christian

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Influence of plane mixed-mode loading on the kinking angle of clinchable metal sheets - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Procedia Structural Integrity)
Keywords: General Engineering; Energy Engineering and Power Technology

A Review on the Modeling of the Clinching Process Chain - Part III: Operational Phase - Schramm, Britta; Harzheim, Sven; Weiß, Deborah; Joy, Tintu David; Hofmann, Martin; Mergheim, Julia; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Development of a method for the separate measurement of the growth of internal crack tips by means of the potential drop method - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A statistically based strain energy function for polymer chains in rubber elasticity - Mahnken, Rolf; Mirzapour, Jamil (Archive of Applied Mechanics)
Keywords: Mechanical Engineering

Effects on Process Forces of Individual Milling Tool Edges Depending on the Cutting Angle and Cutting Speed When Milling Cfrp - Clemens, Robin; Barth, Enrico; Uhlmann, Eckart; Zhan, Yingjie; Caylak, Ismail; Mahnken, Rolf (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Innendrückwalzen – Ein innovatives Umformverfahren zur inkrementellen Formgebung von wanddickenkonturierten Rohren mit lokal einstellbaren mechanischen Eigenschaften - Wiens, Eugen

Occupy the Internet: Why we need a Public Service Internet - Unterberger, Klaus; Fuchs, Christian (Building a European Digital Public Space: Strategies for Taking Back Control from Big Tech Platforms)

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)

大数据、社交媒体和数字异化 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (5))

Servizio Pubblico - Fuchs, Christian (Wired Italia 102)

Digital Humanism. A Philosophy for 21st Century Digital Society. SocietyNow Series - Fuchs, Christian

Methodenentwicklung zur Auslegung geklebter Verbindungen aus hochfestem Stahl unter Berücksichtigung betriebsrelevanter Beanspruchungen im Landmaschinen- und Anlagenbau - Göddecke, Johannes; Meschut, Gerson; Göhrs, Tim; Große Gehling, Manfred

Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson

Application of Thermal Neural Networks on a Small-Scale Electric Motor - Kirchgässner, Wilhelm; Wöckinger, Daniel; Wallscheid, Oliver; Bramerdorfer, Gerd; Böcker, Joachim (IKMT 2022; 13. GMM/ETG-Symposium)

Zu Online-Vergleichsportalen und deren Auswirkungen auf den Markt - Eine wettbewerbspolitische Analyse - Hensel, Jason

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Ecological validity in exercise neuroscience research: A systematic investigation - Chang, Melissa; Büchel, Daniel; Reinecke, Kirsten; Lehmann, Tim; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Triggering instabilities of polymer solution suspensions under uniaxial extension (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Instability analysis of suspensions with a polymer solution matrix (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Transform the Internet: Why we Need a Public Service Internet - Fuchs, Christian; Unterberger, Klaus (Public Value Texte)

Don’t Start from Scratch: A Modularized Architecture for Business Model Development Tools - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Software Business - 13th International Conference, ICSOB 2022, Bolzano, Italy, Proceedings)

Designing Platforms for Crowd-based Software Prototype Validation: A Design Science Study - Gottschalk, Sebastian; Parvez, Sarmad; Yigitbas, Enes; Engels, Gregor (Product-Focused Software Process Improvement - 23rd International Conference, PROFES 2022, Jyväskylä, Finland, Proceedings)

UCAI 2022 - 3rd International Workshop on User-Centered Artificial Intelligence - Buschek, Daniel; Hauptmann, Hanna; Heuer, Hendrik; Loepp, Benedikt; Riener, Andreas; Yigitbas, Enes (Proceedings of the Mensch Und Computer 2022 (MuC ’22))

Design and Evaluation of a Collaborative UML Modeling Environment in Virtual Reality - Yigitbas, Enes; Gorissen, Simon; Weidmann, Nils; Engels, Gregor (International Journal on Software and Systems Modeling (SoSyM))

Rezension zu: Michaela Eigmüller und Mathilde Wohlgemuth (Hrsg.): Schützen – Das Buch. 500 Jahre Kulturgeschichte in Süddeutschland, lllerbeuren 2021 - Leineweber, Jonas (Bayrisches Jahrbuch für Volkskunde)

Algorithms as complementary abstractions. Published online first 2022 - Matzner, Tobias (New Media & Society)

Hannah Arendt: Challenges of Plurality - Matzner, Tobias; Robaszkiewicz, Maria

Far-field Calculation from magnetic Huygens Box Data using the Boundary Element Method - Marschalt, Christoph; Schroder, Dominik; Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Sievers, Denis; Forstner, Jens (2022 Smart Systems Integration (SSI))

Detection of Defects on Irregularly Structured Surfaces using Supervised and Semi-Supervised Learning Methods - Sander, Tom; Lange, Sven; Hilleringmann, Ulrich; Geneis, Volker; Hedayat, Christian; Kuhn, Harald (2022 Smart Systems Integration (SSI))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Flexible source of correlated photons based on LNOI rib waveguides - Ebers, Lena; Ferreri, Alessandro; Hammer, Manfred; Albert, Maximilian; Meier, Cedrik; Förstner, Jens; Sharapova, Polina R. (Journal of Physics: Photonics)
Lithium niobate on insulator (LNOI) has a great potential for photonic integrated circuits, providing substantial versatility in design of various integrated components. To properly use these components in the implementation of different quantum protocols, photons with different properties are required. In this paper, we theoretically demonstrate a flexible source of correlated photons built on the LNOI waveguide of a special geometry. This source is based on the parametric down-conversion (PDC) process, in which the signal and idler photons are generated at the telecom wavelength and have different spatial profiles and polarizations, but the same group velocities. Distinguishability in polarizations and spatial profiles facilitates the routing and manipulating individual photons, while the equality of their group velocities leads to the absence of temporal walk-off between photons. We show how the spectral properties of the generated photons and the number of their frequency modes can be controlled depending on the pump characteristics and the waveguide length. Finally, we discuss special regimes, in which narrowband light with strong frequency correlations and polarization-entangled Bell states are generated at the telecom wavelength.
Keywords: tet_topic_waveguide

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Modeling and Characterization of a 3D Environment for the Design of an Inductively Based Locating Method by Coil Couplings - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2022 Smart Systems Integration (SSI))

Flowability of polymer powders at elevated temperatures for additive manufacturing - Rüther, Moritz Johannes; Klippstein, Sven Helge; Schmid, Hans-Joachim

Mechanical joining in versatile process chains - Meschut, Gerson; Merklein, Marion; Brosius, Alexander; Bobbert, Mathias (Production Engineering)
The use of mechanical joining technologies offers the possibility of joining mixed material structures, which are used in particular in lightweight construction. An integrated securing of the joinability in versatile process chains is currently hardly possible as the number of combinable tool variants as well as variable force- and path-based process parameters is infinite. A versatile process chain, i.e. a sequence of all the processes and process steps required for product manufacturing, enables targeted changes to the semi-finished product, the joint, the component or the joining process that exceed the originally planned extend while still ensuring joinability. In detail, it leads to a unique joint with its own mechanical property profile, which, against the background of the resulting infinite number of combinations, makes it impossible to secure the joinability on the conventional experimentally based approach without extensive safety factors. The Transregional Colaborative Research Center 285 (TCRC285), which also initiated this special issue, is intended to enable mechanical joining technology to be versatile in the sense of high application flexibility. This is to be achieved with a numerical representation of the complete process chain from the incoming semi finished product via the joining part production and the joining process to the property profile of the joint in the operating phase. Thus a predictability of the joinability can be achieved and improvements in the individual life cycles of a joint can be realized by grasping the cause-and-effect relationships. On the basis of this knowledge, new possibilities for intervention in the joining process are to be created for the adaptation of the joining processes. With the aid of the methods developed for this purpose, tools will later be available to the end user to substitute the large number of mechanical joining processes or joining task-specific configurations with a smaller number of adaptable processes. This expands the flexibility in material choices, enabling challenges in environmental issues and sustainability to be overcome.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Untersuchung von Klebverbindungen für Batteriegehäuse - Schmolke, Tobias; Meschut, Gerson; Meinderink, Dennis; Rieker, Florian; Grundmeier, Guido (adhäsion KLEBEN & DICHTEN)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Influence of the incident angle on the OCT measurement during remote laser beam welding - Werner, Matthias; Wagner, Jonas; Ribbeck, Florian; Hensel, Simon; Goth, Klaus; Graf, Thomas; Meschut, Gerson (Procedia CIRP)
Keywords: General Medicine

Thomas Nyckel, Isabel Schmiedel, und Florian Sprenger - Shnayien, Marie-Luise; Engemann, Christoph (The Lab Book. Situated Practices in Media Studies)

ROBOTER BAUEN, PROGRAMMIEREN LERNEN, DIGITALE KULTUREN VERSTEHEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über Arduino in medienwissenschaftlicher Lehre und Forschung - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

FORSCHUNG (BE-)SCHREIBEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über medienwissenschaftliche Laborbücher - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

Arduino - Engemann, Christoph; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (The Lab Book. Situated Practices in Media Studies)

FORSCHUNG (BE-)SCHREIBEN - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Marie-Luise; Sprenger, Florian (Open Media Studies)

Benachteiligtenförderung - Heisler, Dietmar; Schemmer, Susanne (Psychische Belastungen in der Berufsbiografie. Interdisziplinäre Perspektiven.)
Eine Ausbildung meistern, am Erwerbsleben teilnehmen: Das ist angesichts psychischer Belastungen sehr herausfordernd. Und auch für die begleitenden Pädagoginnen und Pädagogen erwächst aus den vielfältigen Symptomatiken die Aufgabe, Unterstützungsmaßnahmen individuell zu gestalten. In dem interdisziplinär angelegten Band wird psychische Belastung erstmals als Querschnittsphänomen aus unterschiedlichen Fachperspektiven betrachtet. Autorinnen und Autoren aus Berufspädagogik, Sonderpädagogik, Sozialpädagogik, Psychologie und Sozialpsychiatrie diskutieren die nachschulischen beruflichen Bildungsprozesse und Unterstützungsangebote zur Teilhabe am Erwerbsleben.

Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern
Über zwei Jahre prägte die Corona-Pandemie unser Leben. Auch für die Berufsbildung blieb das nicht ohne Konsequenzen. Rückblickend wird die Pandemie als „Brennglas“ bezeichnet, in dem sich die Herausforderungen des Bildungswesens bündelten und zeigten. Die Beiträge des vorliegenden Bandes befassen sich mit den konkreten Folgen der Pandemie für verschiedene Bereiche beruflicher Bildung. Ein weiterer Fokus liegt auf der Gestaltung und Wirkung des Distanzlernens in Schule, Betrieb und Hochschule. Zentrale Entwicklungen und ihre Effekte werden bilanziert und reflektiert. Die Beiträge des vorliegenden Bandes benennen nicht nur Desiderate und Schwächen im System beruflicher Bildung, sondern weisen auch auf Chancen und Potenziale hin.
Keywords: Pandemie; Homeschooling; Digitalisierung; Ausbildung; Distanzlernen

Gebäude und Lernumgebungen von Pflegeschulen in Thüringen und Nordrhein-Westfalen - Heisler, Dietmar (Handbuch: Gebäude Berufsbildender Schulen)
Im Handbuch steht die räumliche Gestaltung Berufsbildender Schulen im Fokus. Mit rund 3500 Gebäuden repräsentieren Berufsbildende Schulen in Deutschland ihre besondere berufsorientierte Ausbildungsform. Aber auch in dieser Schulform spielt das Thema Lernraumgestaltung als „dritter Pädagoge" eine zunehmend wichtige Rolle. Trotzdem wird der Neu- und Umbau Berufsbildender Schulgebäude nur selten zwischen Planenden, Lehrenden und Lernenden diskutiert. Um diese Lücke zu schließen, verknüpfen die über 70 Autoren und Autorinnen des Sammelbandes architektonische, Berufsbildungs- und lernorganisatorische Aspekte zu einem neuen Ansatz für eine interdisziplinäre und integrative Planung dieses Lernraums. Im Zentrum des Bandes stehen insbesondere die Möglichkeiten des Zusammenwirkens von Architektinnen und Architekten, Lehrkräften und Lernenden.

Schulbauten aus Sicht der Beruflichen Fachrichtung Körperpflege - Heisler, Dietmar (Handbuch: Gebäude Berufsbildender Schulen)
Im Handbuch steht die räumliche Gestaltung Berufsbildender Schulen im Fokus. Mit rund 3500 Gebäuden repräsentieren Berufsbildende Schulen in Deutschland ihre besondere berufsorientierte Ausbildungsform. Aber auch in dieser Schulform spielt das Thema Lernraumgestaltung als „dritter Pädagoge" eine zunehmend wichtige Rolle. Trotzdem wird der Neu- und Umbau Berufsbildender Schulgebäude nur selten zwischen Planenden, Lehrenden und Lernenden diskutiert. Um diese Lücke zu schließen, verknüpfen die über 70 Autoren und Autorinnen des Sammelbandes architektonische, Berufsbildungs- und lernorganisatorische Aspekte zu einem neuen Ansatz für eine interdisziplinäre und integrative Planung dieses Lernraums. Im Zentrum des Bandes stehen insbesondere die Möglichkeiten des Zusammenwirkens von Architektinnen und Architekten, Lehrkräften und Lernenden.

"Die sehen mich als irgendwas zwischen Schulsozialarbeiter und Sonderpädagoge" - Ergebnisse einer Interviewstudie zur Rolle pädagogischer Fachkräfte in multiprofessionellen Teams an inklusive Schulen - Grüter, Sandra; Hölz, Svenja; Neumann, Phillip; Lütje-Klose, Birgit (Zeitschrift für Inklusion)
Keywords: Multiprofessionelle Teams; Kooperation; Professionalisierung; Schulentwicklung; Inklusion

Boosting artificial intelligence in design processes by the use of additive manufacturing - Ott, Manuel; Meihöfener, Niclas; Koch, Rainer (Proceedings of the 33rd Annual International Solid Freeform Fabrication Symposium 2022)
Additive manufacturing offers the option of converting digital prototypes into real structures as quickly as possible by the special property of tool-free manufacturing. However, this process can only be used at optimum speed if bottlenecks can be effectively avoided. One of these constraints is the design process. Although modern CAD systems allow a significant increase in many areas, this always requires a person with specific skills (e.g. engineer). In the field of AM in particular, more and more powerful software solutions have recently been published which accelerate the Design for Additive Manufacturing, including most CAD-tasks. In many areas, therefore, attempts are already made to automate relevant design steps as much as possible, more and more using neural networks and artificial intelligence. This paper presents how and why such techniques can be used to generate three-dimensional structures quickly and efficiently in cases of deep generative design tasks.

A novel correction method for the shear rate in a couette rheometer (Vortrag) - Rüther, Torben; Jesinghausen, Steffen; Schmid, Hans-Joachim
Keywords: Couette; Rheology; Correction

Multidimensional particle characterization: Centrifugal Differential Mobility Analyzer (Poster) - Rüther, Torben; Schmid, Hans-Joachim

NEW CORRECTION APPROACHES FOR DETERMINING THE TRUE SHEAR RATE IN A COAXIAL-RHEOMETER (Vortrag) - Rüther, Torben; Jesinghausen, Steffen; Schmid, Hans-Joachim

Chow groups of orders in number fields - Kirschmer, Markus; Klüners, Jürgen

RadioML Meets FINN: Enabling Future RF Applications With FPGA Streaming Architectures - Jentzsch, Felix; Umuroglu, Yaman; Pappalardo, Alessandro; Blott, Michaela; Platzner, Marco (IEEE Micro)
Deep neural networks (DNNs) are penetrating into a broad spectrum of applications and replacing manual algorithmic implementations, including the radio frequency communications domain with classical signal processing algorithms. However, the high throughput (gigasamples per second) and low latency requirements of this application domain pose a significant hurdle for adopting computationally demanding DNNs. In this article, we explore highly specialized DNN inference accelerator approaches on field-programmable gate arrays (FPGAs) for RadioML modulation classification. Using an automated end-to-end flow for the generation of the FPGA solution, we can easily explore a spectrum of solutions that optimize for different design targets, including accuracy, power efficiency, resources, throughput, and latency. By leveraging reduced precision arithmetic and customized streaming dataflow, we demonstrate a solution that meets the application requirements and outperforms alternative FPGA efforts by 3.5x in terms of throughput. Against modern embedded graphics processing units (GPUs), we measure >10x higher throughput and >100x lower latency under comparable accuracy and power envelopes.

Johann Rist / Thomas Selle: Neue musikalische Fest-Andachten (1655). Kritisch hg. u. kommentiert v. Johann Anselm Steiger, Berlin/Boston 2020 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Esther Wipfler (Hg.), Das Gesangbuch und seine Bilder. Voraussetzungen, Gestaltung, Wirkung, Wien u.a. 2020 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Tersteegen meets Jazz … Felicia singt: Tersteegen. CD von Felicia Friedrich, Mülheim 2021 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Bound state solutions of Dirac equation: spin and pseudo-spin symmetry in the presence of the combined Manning–Rosen and Yukawa tensor potentials - Ahmadov, A. I.; Nagiyev, Sh. M.; Aydin, C.; Tarverdiyeva, V. A.; Orujova, M. Sh.; Badalov, S. V. (The European Physical Journal Plus)
Keywords: General Physics and Astronomy; Fluid Flow and Transfer Processes

Sprache(n) im kindilchen Aneignungsprozess von (Medien-)Welt. Zur Relevanz der lebensweltlichen Mehrsprachigkeit von Kindergartenkindern aus Einwandererfamilien und mit einem deutsch-türkischen Hintergrund - Günesli, Habib (Mehrsprachigkeit und -kulturaltiät im Konflikt)
Dieser Beitrag basiert auf den Ergebnissen eines im Jahr 2019 abgeschlossenen Promotionsvorhabens im Rahmen des interventiv angelegten, in Dortmund angesiedelten, Forschungsprojekts KidSmart – Medienkompetent zum Schulübergang zu den Mediensozialisationserfahrungen von deutschen, deutsch-türkischen und deutsch-anderen vier und fünf Jahre alten Mädchen und Jungen in den sozialen Feldern Familie und KiTa. Im vorliegenden Beitrag werden die Angaben der Eltern, die mittels halbstandardisierter Fragebögen, und die Aussagen ihrer Kinder, die anhand der Puppet-Interview-Methode gewonnen werden konnten, fokussiert. Vor dem Hintergrund einer globalen und damit zunehmend (sozio-kulturell und sprachlich) pluralen und mediatisierten Welt wird gefragt, inwieweit und wie Kindern in ihrem Aneignungsprozess von (Medien-)Welt die Relevanz ihrer migrationsbedingten Mehrkulturalität und Mehrsprachigkeit vermittelt wird? Es stellte sich heraus, dass migrantisch mehrsprachige und im Besonderen deutsch-türkische Kinder zunächst und hauptsächlich ein- und deutschsprachige Mediennutzer*innen sind, weshalb sie, so ist zu vermuten, auch eine primär ein- und deutschsprachige Aneignung von (Medien-)Welt erfahren werden – insbesondere dann, wenn für sie die Relevanz ihrer Herkunfts- und Erstsprachen nicht ersichtlich ist. Ausgehend von diesen Ergebnissen wird im Rahmen dieses Beitrags perspektivisch nach der Bedeutung und Relevanz der Medienpädagogik zur Förderung der migrationsbedingten Mehrsprachigkeit gefragt und der Blick konkret auf die mehrkulturelle Mediensozialisationsforschung gerichtet, die diese Ausprägung der Mehrsprachigkeit zu ihrem zentralen Forschungsgegenstand machen sollte.
Keywords: Mehrsprachigkeit; Mehrkulturalität; Migration; Mediensozialisation; Migration; Frühe Bildung

Small-scale online simulations in guided-wave photonics - Hammer, Manfred (Integrated Optics: Devices, Materials, and Technologies XXVI)
Online solvers for a series of standard 1-D or 2-D problems in integrated optics will be discussed. Implemented on the basis of HTML/JavaScript/SVG with core routines compiled from well tested C++-sources, the quasi-analytical algorithms require a computational load that can be handled easily even by current mobile devices. So far the series covers the 1-D guided modes of dielectric multilayer slab waveguides and the oblique plane wave reflection from these, the modes of rectangular channel waveguides (in an approximation of effective indices), bend modes of curved multilayer slabs, whispering-gallery resonances (“Quasi-Normal-Modes”) supported by circular dielectric cavities, the hybrid modes of circular multi-step-index optical fibers, bound and leaky modes of 1-D complex multilayers, including plasmonic surface modes, and, with restrictions, quite general rectangular scattering problems in 2-D.
Keywords: tet_topic_waveguide

The “black box” of social commerce platforms-a closer look at users’ activities - Meydani, Elnaz; Düsing, Christoph; Fedrau, Annamaria; Trier, Matthias

Wie die Queen: Die deutsch-jüdische Geschichte einer sehr britischen Schriftstellerin - Ribbat, Christoph

Quasiparticle energies and optical response of RbTiOPO4 and KTiOAsO4 - Neufeld, Sergej; Schindlmayr, Arno; Schmidt, Wolf Gero (Journal of Physics: Materials)
Many-body perturbation theory based on density-functional theory calculations is used to determine the quasiparticle band structures and the dielectric functions of the isomorphic ferroelectrics rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenide (KTiOAsO4). Self-energy corrections of more than 2 eV are found to widen the transport band gaps of both materials considerably to 5.3 and 5.2 eV, respectively. At the same time, both materials are characterized by strong exciton binding energies of 1.4 and 1.5 eV, respectively. The solution of the Bethe-Salpeter equation based on the quasiparticle energies results in onsets of the optical absorption within the range of the measured data.